Gerakan Ekofeminisme dalam Mewujudkan Tujuan Pembangunan Berkelanjutan (SDG’s) - Fuadi, Rusydan Fauzi; Sari, Ramadhanita Mustika (IAIN Syekh Nurjati Cirebon, 2023)
ABSTRACT: Ecofeminism is a movement that was born from the anxiety of women in various parts of the world and from various professions who oppose injustice against women who are always associated with unfounded myths. Therefore, women environmental activists continue to fight against the stigma that has spread in society and try to rise to play a role in saving the earth so that an ideal, environmentally friendly and women-friendly life is realised. The ecofeminism movement is in line with the Sustainable Development Goals (SDG's), of which two of the 17 pillars are the main focus of the ecofeminism movement, namely the Gender Equality pillar and the Climate Change Management pillar. In addition, Islam as a religion of rahmatan lil alamin views ecology and gender equality as an important element that is interconnected with each other so as to create Hablum minal Alam or a more harmonious relationship with nature.Keywords: Ecofeminism, Environment, Ecology, SDG's.